On modeling problem of optimizing the environmental performance of ship power plant with reciprocating thermal engines as complex technical systems, taking into account operating costs and risk indices when operating on multi-grade fuels - V. R. Vedruchenko; A. V. Shtib; I. I. Malakhov (Омский научный вестник)
On modeling the problem of optimizing the environmental performance of a ship power plant with reciprocating thermal engines as complex technical systems, taking into account operating costs and risk indices when operating on multi-grade fuels. A mathematical model of the problem of optimizing the environmental performance indicators of technical complex systems is presented based on the criterion of minimum total costs. The developed optimization criterion allows to take into account both operational costs and accident risk indicators for the operation of complex systems. The efficiency of the developed models is confirmed by the results of the simulation.